The Implementation of Higher Education Institutions to Dialogue Communication Principles via Twitter - Al-Saify, Hassan; Aisha , Fouda; Hashem, Mohamed; Osama, Sally; Darwish, Shaimaa (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to investigate how public relations are used in Saudi universities' social media and to what extent they benefit from the advantages of these platforms in higher education institutions. Method: The study used a descriptive method, and content analysis was used to collect the data. The content published by public relations on the official accounts of King Faisal University, King Abdulaziz University, and Al Faisal National University on Twitter was analyzed in light of the principles of dialogue communication theory by Kent and Taylor as well as models of public relations practice. The study was conducted during April, May, and June 2022, representing the study periods, exams, and summer vacation. Results: The results revealed that Twitter is mainly used by public relations in Saudi universities for publishing and promotion. The results also showed differences between universities in dialogue with their public and models of public relations practice. Government universities were less likely to apply the principles of dialogue communication and only interacted with the public on rare occasions, using it as a tool for promotion, publicity, and information in one direction, limiting the benefits of two-way dialogue. Conclusion: Universities need to pay more attention to dialogue with the public to maximize the benefits of untapped communicative abilities.